Cultural Perceptions of Healthy Eating in the Latino Multiethnic Population in Boston, MA (P04-097-19) - Caballero-Gonzalez, Areli (Curr Dev Nutr, 2019)
OBJECTIVES: Little is known about the deeply-rooted cultural beliefs and attitudes towards healthy eating of Hispanics/Latinos in the U.S. We aimed to identify existing dietary beliefs and attitudes of Latino adults living in the Boston metro area and to determine ethnic-specific differences in such, using a mixed-methods approach. METHODS: All participants were self-identified Latinos living in the Boston metro area, recruited in community or public settings. For the qualitative portion, 17 in-depth interviews were conducted in Spanish among men and women aged 30–60 years from multiple Latino heritages. Questions focused on cultural beliefs and attitudes towards healthy eating. Thematic analysis using deductive coding was conducted by heritage grouping. For the quantitative portion, 125 surveys with scale-based questions on attitudes and motivators of healthy eating were collected among Latino participants 25–65 years old. Frequency analysis was conducted in SAS v9.4. RESULTS: Common themes emerging from the interviews amongst all heritages included an awareness of the difference in taste of US-based foods when compared to foods from their country of origin, need for education/skills on healthy eating, and common barriers when choosing healthy foods (i.e.,: lack of time, access, and cost). Dominicans and Puerto Ricans mentioned weight loss, appearance, and health (to care for their family) as a main incentive to eat healthier, while other Latino heritages mentioned variety, reduced costs, and being a role model for their family. Heritage-specific dietary traditions and foods were noted. The survey analysis showed that 93.6% of all Latinos agreed that eating healthy will keep them healthy, 88.9% agreed that it will help them look good, and 86.2% agreed that it should be done together as a family. Differences by heritage were noted in most statements, such as fewer Puerto Ricans agreeing on eating healthy for health, and more Central Americans agreeing on the role of family. CONCLUSIONS: Latinos have shared and ethnic-specific cultural beliefs and motivations for healthy eating. This information will help create tailored dietary interventions for the Latino community in Boston using deep-cultural strategies. FUNDING SOURCES: NHLBI Mentored Career Development Award to Promote Faculty Diversity: K01-HL120951.